The Portraits of Bataknese and Sundanese Cultural Identity towards Marriage Custom in Lamaran Movie - Sihombing, Lambok Hermanto (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Indonesia is a diverse country, home to numerous tribes, religions, languages, and traditions. Each region of Indonesia has its own set of traditions. One of the most intriguing customs to observe is the customary marriage law, especially for Bataknese and Sundanese. They both have certain rules when they have to find their couple. They inherit their marriage custom for the sake of cultural identity. Thus, those marriage rules are represented in the Lamaran movie. In this scientific study, the author aims to analyze the portraits of Bataknese and Sundanese cultural identity towards their marriage custom in the Lamaran Movie. In order to help the author doing this analysis, Mise En Scene approach from Manon de Reeper and the theory of Cultural Identity from Stuart Hall are used for this study. The result of this study indicates that either Bataknese or Sundanese attempts to pass down their marriage custom as it influences their identity in the future.